Parental apprehension, knowledge, attitudes, and practices regarding COVID-19 infection in children: A cross-sectional study - Raghava Badabagni,; Raj Kiran Donthu,; Prudhvi Raju Pericherla V,; Hari Krishna Koushik Bodagala,; Pardha Saradhi, (Asian Journal of Medical Sciences, 2023)
Background: With the anticipation of the coronavirus disease 2019 (COVID-19) third wave, there were reports of increased rates of infection among children. So naturally, there will be apprehension among parents regarding this. Knowledge, attitudes, and practices (KAPs) play an important role in effectively controlling the infection. Aims and Objectives: The study is an attempt to understand parental apprehension and their KAP regarding COVID-19 infection in children. Materials and Methods: A total of 367 parents participated. Statistical analysis of the data was performed using R language. Results: Higher scores of knowledge were reported among higher age (P=0.003), higher education (P<0.001), professionals (P<0.001), urban area (P<0.001), and two or more children (P=0.022). Good practices were noted among unemployed (P<0.001), Hindu religion (P=0.045), and single child (P=0.002). Higher educated and employed had good knowledge, but practices were better among unemployed and illiterate. Knowledge was positively correlated with attitude (r+0.54, P<0.001, 95% CI [0.47, 0.61]) and practices (r+0.26, P<0.001, 95% CI [0.17, 0.36]); and attitudes with practices (r+0.32, P<0.001, 95% CI [0.22, 0.41]). Conclusion: The study finds that generally, parents have good KAP toward COVID-19. However, they have limited knowledge regarding COVID-19 infection in children contributing to parental apprehension. It is time we spread awareness on KAPs regarding COVID-19 infection in children.